Improving flow of patients with hyperglycaemia (non-DKA/non-HHS) from the emergency department - Vithiya Umaipalan; Omar Mustafa; Sophie Harris (Future Healthcare Journal)
Introduction: Hyperglycaemia is commonly encountered in the emergency department (ED). Diabetic ketoacidosis (DKA) or hyperosmolar hyperglycaemic state (HHS) require admission, while hyperglycaemia (non-DKA/non-HHS) can be managed in ambulatory care units (ACUs).1,2 Early identification and prompt administration of appropriate insulin doses are important to reduce the length of stay in ED and to avoid admission.3,4 An initial survey among ED clinicians revealed low confidence in managing patients with non-DKA/non-HHS hyperglycaemia despite availability of Trust guidelines. The aim of this project was to improve management of non-DKA/non-HHS hyperglycaemia in ED. Methods: A quality improvement methodology using plan–do–study–act (PDSA) cycles and run charts was used for this project. Data analysis was carried out at baseline and monthly thereafter. The first 10 cases with hyperglycaemia as the primary diagnosis with no other reason for admission were analysed monthly. The primary outcome measure was the length of stay in ED. The process measurements were time from arrival to glucose check, time from glucose check to first dose of insulin and percentage of appropriate insulin doses given according to the Trust guidelines.PDSA cycle 1: education sessions for doctors (residents/consultants) and ED nurses on management of hyperglycaemia in EDPDSA cycle 2: revision of the guidelines to incorporate the pathways of patient journeys from ED to ACUs and QR codes for patient education.PDSA cycle 3: improved accessibility of the guidelines, smart phrases in the electronic health system and creation of a diabetes page on a mobile app. Results and discussion: There were decreases in the length of ED stay for patients with hyperglycaemia (Fig 1). However, there is no improvement in the time from admission to glucose check or insulin administration. After the third PDSA cycle, there were no readmissions and a higher percentage of patients received appropriate insulin doses (Table 1). Conclusion: This iterative quality improvement project shortened the length of stay for patients being admitted to ED with hyperglycaemia, with no readmissions noted. It is unclear how the education of doctors contributed to the reduction of the length of stay for hyperglycaemia without affecting the process measures. Possible reasons include the effective subsequent management of hyperglycaemia, early discharge planning and ACU follow-up, and diabetes team input. Further analysis of the average ED length of stay for other conditions, utilisation of ACUs over the same period and resurvey of ED clinicians would provide more understanding of other factors contributing to the length of stay.Lessons learned and next stepsImplementing blood glucose and ketone checks for all patients with diabetes on arrival would reduce the delay in glucose checking and help to identify patients in need of diabetes consultation when presenting to the ED for non-diabetes-related problems.Healthcare professional education in the ED was difficult due to unpredictability of the ED workload and rotation of resident doctors. Bedside opportunistic teaching and dedicated teaching hours were found to be more practical. This highlighted the need to develop an inpatient diabetes education plan.